1987
DOI: 10.1254/jjp.43.91
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-threo-3,4-dihydroxyphenylserine (L-DOPS), an immediate precursor of norepinephrine, on the cerebral blood flow in rats.

Abstract: Abstract-L-threo-3,4-Dihydroxyphenylserine (L-DOPS), a norepinephrine (NE) precursor, 3 mg/kg, i.v., increased the cerebral blood flow (CBF) in both the striatum and hippocampus as well as the mean arterial blood pressure (MABP) in urethane-anesthetized rats, as NE infusion did. The L-DOPS induced increase in CBF was inhibited by benserazide (3 mg/kg/hour), a peripheral aromatic L-amino acid decarboxylase inhibitor, and propranolol (3 mg/kg, i.p.), a 19-adrenoceptor blocker as well. These results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The effects of raising CNS NA levels on MCP-1 expression were tested by treating 3-month-old female C57Bl6 mice with the synthetic NA precursor L-DOPS, which is converted by the enzyme L-AAAD to NA (Sato et al 1987;Kikuchi et al 2000). Mice were treated for 10 days with a daily injection of L-DOPS (200 mg/kg i.p.)…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of raising CNS NA levels on MCP-1 expression were tested by treating 3-month-old female C57Bl6 mice with the synthetic NA precursor L-DOPS, which is converted by the enzyme L-AAAD to NA (Sato et al 1987;Kikuchi et al 2000). Mice were treated for 10 days with a daily injection of L-DOPS (200 mg/kg i.p.)…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…By administering desipramine, the endogenous NA reuptake system is inhibited. Another approach was to administer the synthetic NA precursor L-threo-3,4-dihydroxyphenylserine (L-DOPS) which is converted to NA by L-aromatic amino acid decarboxylase (L-AAAD) (Sato et al 1987;Kikuchi et al 2000). To confine this conversion to the brain, L-DOPS was used in combination with benserazide (an inhibitor of L-AAAD) that does not cross the blood brain barrier.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 ' 5 Benserazide, an extracerebral decarboxylase inhibitor, at a high dose (1 mg/kg or more) may penetrate the blood-brain barrier and inhibit the decarboxylation of DOPS to norepinephrine. 5 An addition of DOPS increases nerve growth factor (NGF) synthesis in cultured mouse L-M fibroblast and astroglial cells, and this effect is not blocked by treatment See Editorial Comment, page 1432 with decarboxylase inhibitor.…”
mentioning
confidence: 99%
“…L-DOPS is known to activate β-adrenergic receptors (33) and dilate brain blood vessels (34). Furthermore, Sato et al (35) reported that L-DOPS increased CBF in urethane-anesthetized rats, and suggested that such effects might be mediated by the action of NE formed from L-DOPS in the brain, through stimulation of βadrenoceptors. Our results confirmed that serum NE concentrations increased significantly following oral administration of L-DOPS, which might contribute to the improvement in CBF.…”
Section: Discussionmentioning
confidence: 99%